Análise de desempenho, estabilidade e confiabilidade de estações de tratamento de esgoto - Lobão, José Reges da Silva (2009)
The domestic sewers are composites, in part, for human dejections that can contain pathogenic organisms, where also are verified that, the present organic substance in these residues, when introduced to the sources, provokes the consumption of the oxygen dissolved in the water. In this direction, the treatment of effluent domestic servants is essential to prevent the proliferation of illnesses of hídrica propagation and protection of biota of the courses of agua. Trustworthiness is the probability of an item of playing its function adequately, in accordance with the specified conditions, for a foreseen period of time. Being thus, one becomes essential that the processes of treatment of sewers are evaluated in relation to the trustworthiness, supplying information that can subsidize the election of one definitive system of treatment and allowing the evaluation of the real performance of a ETE, as for the attendance to the established legal requirements or to the defined goals of efficiency during the project. The methodology adopted in this study was to the boarding, qualitative and quantitative of parameters, understanding evaluation of efficiency, trustworthiness and stability. The analysis instruments had been disponibilizados and considered for METCALF; EDDY (1991) and NIKU et al. (1979) and use of tools of Excel. It presents results generated from carried through analyses, in agreement the manipulation of data supplied for the CAGECE. A bibliographical research was made that resulted in the elaboration of the work, that understands all the carried through analyses and the construction of the compact program of operational control for ETEs. The present work concludes the necessity of implantation of this study in the estruturação of projects, whose objectives understand to allow that the stations of treatments of sewers take care of to the norms, fulfilling commitments with the environment and with the society, considering a new relative public vision to the residuary water treatment, and determining a good relation enters the sanitation company all and the social system, favoring the improvement of the current situation.